Aloe-emodin induces apoptosis in human oral squamous cell carcinoma SCC15 cells - Qihong Li; Jun Wen; Kaitao Yu; Yao Shu; Wulin He; Hongxing Chu; Bin Zhang; Cheng Ge (BMC, 2018)
Abstract Background Oral and pharyngeal cancer is the most common malignant human cancers. Chemotherapy is an effective approach for anti-oral cancer therapy, while the drug tolerance and resistance remain a problem for oral cancer patients. Aloe-emodin, rhein and physcion are classified as anthraquinones, which are the main pharmacodynamic ingredients of Rheum undulatum L.. This study was undertaken to investigate whether aloe-emodin, rhein and physcion show inhibiting growth and inducing apoptosis in oral squamous cell carcinoma SCC15 cells. We found that aloe-emodin show inhibiting growth and inducing apoptosis in oral squamous cell carcinoma SCC15 cells, we also investigated the underlying mechanisms of apoptosis induced by aloe-emodin. Methods Thiazolyl blue tetrazolium bromide (MTT) test was used to detect cell proliferation. Cell apoptosis was detected by flow cytometry. We also used western blot analysis to detect the potential mechanisms of apoptosis. Results Aloe-emodin, rhein and physcion inhibit the proliferation of SCC15 cells and the order of inhibition level are aloe-emodin > Rhein > Physcion, the half maximal inhibitory concentrations (IC50) value of aloe-emodin was 60.90 μM at 48 h of treatment. Aloe-emodin treatment resulted in a time- and dose-dependent decrease in cell viability and increased the apoptotic cell ratio. The results of western blotting showed the expression levels of caspase-9 and caspase-3 proteins increased following aloe-emodin treatment. Conclusions Our results revealed that aloe-emodin treatment could inhibit cell viability of SCC15 cells and the potential mechanism of inhibition might be through the induction of apoptosis by regulation of the expression levels of caspase-9 and caspase-3. This indicates that aloe-emodin may be a good agent for anti-oral cancer drug exploring.